Diseño de un suplemento alimenticio en polvo a base de auyama de forma teórica apto para el consumo humano (2022)
For the development of this project, 4 stages were taken into account, of which the first was based on the investigation of the characteristics of the pumpkin in aspects such as: taxonomy, cultivation, nutritional value and uses; presenting a definition, functionality and regulations regarding food supplements in terms of tolerance levels of chemical components, label legends, presentation and types of supplements; In addition, a market investigation was carried out with a client profile, analysis of demand, supply and their behavior; complementing it with surveys carried out in the city of Bogotá D.C.